Numerical analysis of the effects of soil inclusions on the liquefaction susceptibility of horizontally-layered soils - Tisang, Jomalyn G.
With various geotechnical advances, identification and remediation of issues and impact of future hazards which concerns soil engineering have been readily available and easily performed. Liquefaction, being likely to develop after an earthquake, is one interesting topic to explore. One can never really prevent liquefaction from occurring, but its effects can be alleviated by introduction of soil inclusions. Seed and Idriss have proposed a simple method in the evaluation of soil liquefaction. It starts with the quantification of two stresses - the cyclic stress ratio (CSR) and the cyclic resistance ratio (CRR). The CSR are the resulting stresses of an earthquake or ground movement, while the CRR are stresses required to instigate liquefaction in the soil. These two stresses can be compared to produce a value for the factor of safety for a certain soil depth. SHAKE91 is a convenient software to use for the computation of the said stresses; and, for numerical models and simulation, GeoStudio QUAKE/W was used for creating two-dimensional models to compare the CSR values of non-improved to that of improved. The expected output for this study are juxtaposed charts of the CSR with respect to depth of soil columns showing the noticeable effects of the soil inclusions to the soil - specifically how inclusions minimize the produced liquefaction in the soil when ground motion is induced. The data have yielded slightly different results from what was expected, but the entire study still satisfied the objective of determining the effects of soil inclusions to the soils liquefaction potential. Soil inclusions do not necessarily prevent the development of high CSR values - it actually produced CSR values higher than that of soil columns without improvement. However, this is due to the introduction of a stiffer material as a replacement of some parts of the soil. For the entirety of the study and as observed in the resulting data, it can be concluded that soil inclusions or jet grouted cement is an efficient remedy for minimizing the effects of liquefaction in the soil.